Cannabinoid receptor 1 gene (CNR1) and susceptibility to a quantitative phenotype for hebephrenic schizophrenia - Chavarría Siles, Ivan M. (2008)
Functional alterations of components of the endogenous cannabinoid system, in particular of the cannabinoid receptor 1 protein (CB1), are hypothetical contributors to many of the symptoms seen in schizophrenia. Variants within the cannabinoid receptor 1 gene (CNR1) have been shown to be directly associated with the hebephrenic form of schizophrenia in a Japanese population. This finding, however, has yet to be replicated. In the present study we sought to study the same (AAT)n-repeat microsatellite of the CNR1 gene which showed association to hebephrenic schizophrenia in Japan, and to investigate whether this microsatellite showed association to a hebephrenic type of schizophrenia in a family-based association study in a population of the Central Valley of Costa Rica. The Lifetime Dimensions of Psychosis Scale and a best estimate consensus process were utilized to identify subjects with schizophrenia who had an elevated lifetime dimensional score for negative and disorganized symptoms, which we used as a proxy for "hebephrenia." Using the Family Based Association Test we found association of these hebephrenic subjects and the (AAT)n-repeat marker of the CNR1 (multi-allelic P = 0.0368). Our hypothesis that an association with the (AAT)n-repeat marker of CNR1 would not be found with the more general type of schizophrenia was also confirmed. Schizophrenic subjects with prominent lifetime scores for disorganization and negative symptoms (dimension for hebephrenia) are associated with the CNR1 gene and present a type of symptomatology that resembles chronic cannabinoid-induced psychosis. The current finding points to the possibility of different genetic and pathophysiologic mechanisms underlying different types of schizophrenia.